Effects of cortisol on the intestinal mucosal immune response during cohabitant challenge with IPNV in Atlantic salmon (Salmo salar) - Niklasson, Lars; Sundh, Henrik; Olsen, Rolf Erik; Jutfelt, Fredrik; Skjødt, Karsten; Nilsen, Tom Ole; Sundell, Kristina (PLoS ONE, 2015)
-